2013
DOI: 10.1097/dcr.0b013e318273f56f
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Endoscopic Microsurgery for Residual Rectal Cancer (ypT0-2) Following Neoadjuvant Chemoradiation Therapy

Abstract: A local failure rate of 15% after transanal endoscopic microsurgery for patients with residual rectal cancers restricted to the bowel wall (ypT0-2) may limit the indication of this procedure to highly selected patients as an alternative to standard radical total mesorectal excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 22 publications
1
79
0
7
Order By: Relevance
“…The high number of ypT2 and ypT3 operated tumors could explain the 10.3% recurrence rate observed in the present study. Higher recurrence rates in stage II and III patients have previously been observed 27,28 . Both surgeon and patients should be aware this risk when contemplating any local excision procedure.…”
Section: Resultsmentioning
confidence: 85%
“…The high number of ypT2 and ypT3 operated tumors could explain the 10.3% recurrence rate observed in the present study. Higher recurrence rates in stage II and III patients have previously been observed 27,28 . Both surgeon and patients should be aware this risk when contemplating any local excision procedure.…”
Section: Resultsmentioning
confidence: 85%
“…The authors addressed that when complete pathological response was achieved (ypT0), local recurrence was 0% and systemic recurrence was 4%, in ypT1 tumors, local recurrence was 2% and systemic recurrence was 7%, in ypT2 tumors, both local and systemic recurrence rose to 7%, while when there was no response (ypT3), the local recurrence was 21% and the systemic recurrence was 12% after local excision. Similarly, a prospective study [94] of 27 patients with ypT0-2 tumors in the lower rectum after neoadjuvant CRT, treated by TEM, showed a local recurrence rate of 15% within a median follow-up of 15 mo. Lymphovascular invasion was disclosed as the only independent dismal prognostic factor for local failure (P = 0.04), while tumor size, ypT status, T-status downstaging, lateral/radial margins and tumor regression grade, did not reach statistical significance.…”
Section: Long-term Results Studies On the Oncological Outcome Followimentioning
confidence: 99%
“…27 These results are quite improved over the prior studies which showed up to a 15% recurrence rate. 28 Certainly, there will need to be improvements in our ability to characterize tumor response to neoadjuvant therapy radiologically before local excision can be routinely recommended.…”
Section: Local Therapymentioning
confidence: 99%